Professional self-determination of schoolchildren: trends and difficulties in formation - N. A. Nekhoroshikh (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. Currently, in Russia, the fundamental ideas of career guidance for the younger generation are embedded in a single model of professional orientation. According to this model, career guidance is built into a system based on general education organizations for students in grades 6-11 and is aimed at forming their readiness for a conscious choice of a future profession – professional self-determination. Goal. Highlighting current trends in working with schoolchildren to form their readiness for professional self-determination and identifying possible difficulties along the way.Materials and methods. The research is based on the analysis and pedagogical interpretation of modern scientific research that highlights the issues of career guidance for students in general education institutions and the current regulatory documents governing this process. The implementation of a set of diagnostic techniques made it possible to identify a number of problems related to professional self-determination among ninth graders. The empirical study covered students of the 9th non-core grade of a secondary school, as they had not been able to determine their education profile earlier.Results and discussion. In the course of the work, it was found that many schoolchildren experience uncertainty in choosing a profession. Significant gaps in students’ knowledge of the basic concepts of professional activity have been identified. The predominance of social and material factors creates conflicts and difficulties for adolescents in making a final decision about choosing a profession. The lack of a profile orientation among students suggests that they have the least concrete ideas about their future professional path. The results of an empirical study conducted among ninth graders of secondary schools provide the basis for the following conclusions. A significant part of the respondents are in a state of “crisis of choice” for their future profession. The data obtained during diagnostic procedures give grounds to draw conclusions about the presence of specific difficulties in adolescents in the process of their professional self-determination. Conclusion. The author substantiates and points out the need to continue purposeful work on the formation of professional identity among schoolchildren, taking into account the difficulties identified among schoolchildren.